СОЦІАЛЬНІ МЕРЕЖІ ЯК СЕРЕДОВИЩЕ ЗАСТОСУВАННЯ КОМУНІКАТИВНИХ ПРАКТИК - Равлюк, Тетяна (Київ, 2023)
The modern development of society, including the Ukrainian one, is impossible without the use of innovative information and communication technologies, which also include social media. Numerous scientific studies actualize the phenomenon of social networks, the peculiarities of their use, the impact on the individual, the search for opportunities to create a constructive virtual space. The specifics of the use of communication practices in social networks are considered. Scientific approaches to understanding the concept of "communication" are stated, namely: communication as an exchange of information (subject-object); as interpersonal communication (subject-subject); as a social process, a long-lasting interaction in space and time. The concept of "communicative online practices" is defined as a special, continuous, fast, flexible, spontaneous, open type of social practices that unfolds in the virtual communication space. A social network is an interactive website that attracts a large number of participants due to the peculiarity of the communication environment, the ability to quickly find friends, track their life activities through photos, videos, etc. The growth in the number of social media users during the war was confirmed by a study conducted by Global Logic in 2022. The results of a survey of 140 higher education students of Yuriy Fedkovych Chernivtsi National University were analyzed to determine the peculiarities of their use of online communication practices in social media. The majority of respondents indicated that they most often use the practices of distraction and entertainment (77.9%), and the practices of development and self-improvement (72.9%). In order to organize a constructive virtual space, 61.4% of respondents recommend developing a regime for using social media and strictly adhering to it. In order to compare their own answers with the opinions of middle-aged and older people, respondents expressed a desire to propose similar questions to parents and other family members.
Keywords: practice, communication, social media, communication practices